2022
DOI: 10.1080/19490976.2022.2105610
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-fungal metabolic interactions within the microbiota and their potential relevance in human health and disease: a short review

Abstract: The composition of the microbiota is the focus of many recent publications describing the effects of the microbiota on host health. In recent years, research has progressed further, investigating not only the diversity of genes and functions but also metabolites produced by microorganisms composing the microbiota of various niches and how these metabolites affect and shape the microbial community. While an abundance of data has been published on bacterial interactions, much less data are available on the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 146 publications
0
13
0
Order By: Relevance
“…The fungi in the human microbiome, often referred to as the mycobiome, are not broadly included in microbiome or psychobiotics research despite being important for human health. The ways that fungi and bacteria interact, including but not limited to cross-feeding also known as sharing of metabolites (Lapiere and Richard, 2022; see Figure 1 inset) and changing biofilm formation (Zijnge et al, 2010) are important for disease pathogenesis (Sultan et al, 2018) and maintaining health (Bradford and Ravel, 2017). In addition to playing an understated role in maintaining health, fungi are also key to the gut-brain axis (Enaud et al, 2018).…”
Section: Exclusion Of Fungimentioning
confidence: 99%
“…The fungi in the human microbiome, often referred to as the mycobiome, are not broadly included in microbiome or psychobiotics research despite being important for human health. The ways that fungi and bacteria interact, including but not limited to cross-feeding also known as sharing of metabolites (Lapiere and Richard, 2022; see Figure 1 inset) and changing biofilm formation (Zijnge et al, 2010) are important for disease pathogenesis (Sultan et al, 2018) and maintaining health (Bradford and Ravel, 2017). In addition to playing an understated role in maintaining health, fungi are also key to the gut-brain axis (Enaud et al, 2018).…”
Section: Exclusion Of Fungimentioning
confidence: 99%
“…Lower fungal diversity compared to bacterial diversity has been found in many species 65 , 69 . Although fungal populations have lower diversity compared to bacteria, they are considered functionally important for the stability of the microbial ecosystem because there are specific interactions between bacterial and fungal groups that are important for the physiology of the host 65 , 70 . Indeed, in zebrafish it has been shown that exposure of larvae to Debaryomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…While colon mucosal biofilms were shown to be carcinogenic in a genetic mouse model, the role of fungi in such cancer-related biofilm interactions is not investigated to date, to the best of our knowledge 140. Similarly, while interactions that may be mediated via quorum sensing and can act across kingdoms have been reported to exist as reviewed elsewhere,141 this has not been shown in a cancer specific context to date. Studies on bacteria–fungi interactions in health and disease, which may bear relevance to cancer, and their respective mechanisms as reported mainly in in vitro co-culture set-ups, were extensively reviewed in several excellent reviews 142–148…”
Section: Inter-kingdom Fungal Interactions In Cancermentioning
confidence: 98%